Criteria Evaluation in the Formation of Student Competencies - Gulyash, Koshanova; Venera, Mamayeva; Bazarkul, Kulzhagarova; Rakhat, Shuakbayeva; Sholpan, Saparbayeva (Journal of Intellectual Disability - Diagnosis and Treatment, 2018)
Pedagogical education in Kazakhstan has reached a new level of development. Changes occurring in the value, target, functional and other spheres of modern education require adequate identification and scientific and pedagogical comprehension. The essence of these changes, affecting both individual national structures and the world community as a whole, can be designated by the term ‘integration’. Confrontation is replaced by an association that implies a complex interaction between interests of individual subjects of integration and requires a qualitatively new level of management and regulation of such interactions. The dynamics of change in various areas determines the shifts in the geopolitical, economic, social and other conditions of human activity. The objective of this article was to examine evaluation of training in higher education as an integral part of teacher daily work. A questionnaire was administered to a group of teachers, who responded to several items related to these six dimensions: discipline, characteristics of the course, evaluation tools, evaluation practices, communication between teacher and student, and involvement of teachers in improving learning assessment.